DIDATTICA DIGITALE PER LE LINGUE STRANIERE: SFIDE E OPPORTUNITÀ: A cura di Peggy Katelhön (Italiano LinguaDue, 2025)
Contributi di Peggy Katelhön, Elena Landone, Andrea Nava, Laila Paracchini, Luciana Pedrazzini, Martin Ruskov, Giuseppe Sergio, Emanuela Tenca.